2019
DOI: 10.3892/or.2019.7024
|View full text |Cite
|
Sign up to set email alerts
|

The role of GDF15 in bone metastasis of lung adenocarcinoma cells

Abstract: Lung cancer is the most common malignant tumor in China. It often metastasizes to bone, thereby significantly shortening the lives of patients, and reducing their quality of life. However, the efficacy of treatment for bone metastasis of lung cancer at this stage is very limited. The development and clinical application of molecular-targeted drugs for the effective targeted therapy of bone metastasis of lung cancer are urgently required. The growth differentiation factor 15 (GDF15) gene which may be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…The most common sites for lung cancer metastasis are the nervous system, bone, liver, respiratory system and adrenal glands. Bone metastasis is the most common in patients with lung adenocarcinoma (39%) (4). The prognosis and survival rate of patients with advanced lung cancer are very poor, and the survival rate is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The most common sites for lung cancer metastasis are the nervous system, bone, liver, respiratory system and adrenal glands. Bone metastasis is the most common in patients with lung adenocarcinoma (39%) (4). The prognosis and survival rate of patients with advanced lung cancer are very poor, and the survival rate is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…In tumor cells, the TGF-β/Smads signaling pathway is associated with the invasion and metastasis of tumor cells induced by EMT through regulating the downstream transcription factors, such as Snail and α-SMA [29]. Previous research has shown that GDF15 was involved in the migration of colon cancer and lung adenocarcinoma by regulating the TGF-β/Smads signaling pathway [8,12]. In this study, we explored the regulatory role of GDF15 on the TGF-β/Smads signaling pathway in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 regulates various cellular functions in cancers. For example, the high expression of GDF15 inhibited the metastasis of lung adenocarcinoma via regulation of the TGF-β/Smad signaling pathway, and GDF15 plays a vital role in the mediation of proliferation and apoptosis of prostate cancer cells [8][9][10]. In addition, GDF15 activated extracellular regulated protein kinases1/2 (ERK1/2) through autocrine and paracrine to promote the development of breast cancer [11].…”
mentioning
confidence: 99%
“…In addition, psoralen might regulate some physiological process in HCC by increased relevance mRNA levels on endoplasmic reticulum. Growth differentiation factor 15 (GDF15) is a divergent member of the BMP-subfamily of the TGF-β superfamily, which could inhibit the proliferation, migration and invasion, while promoting apoptosis of A549 cells [52]. Induction of ER stress leads to upregulation of several genes such as WARS (tryptophanyl-tRNA synthetase), HERP (homocysteine-inducible ER protein with ubiquitin like domain 1), DNAJC3 (also called P58IPK), ER degradation-enhancing alpha-mannosidase-like 1 (EDEM1) and leads to caspase activation, release of mitochondrial intermembrane proteins and dissipation of mitochondrial transmembrane potential (ΔΨm) [53].…”
Section: Discussionmentioning
confidence: 99%